PROFESSIONAL QUALITY EDUCATION BASED ON ENTREPRENEURSHIP THROUGH INTENSIVE INTERNSHIPS PROGRAM ABROAD - Isdarmanto, Isdarmanto (Kepariwisataan: Jurnal Ilmiah, 2017)
The phenomenon is very significant growth in tourism has been able to create business opportunities so high, but it still not fully captured well by the majority of higher education institutions in particular tourism. In fact their educational programs are still oriented in learning programs for development through academic curriculum that prepares graduates only in accordance with the needs of industry. Most graduates oriented as job seekers, but not as the creator of the workplace (job creators). It is necessary for the implementation of innovative educational development program that is able to change the mindset and creativity of graduates integrated focus on aspects of entrepreneurship. Needs and challenges for students who have the competence and dare to create business opportunities that are relevant to the development of a highly competitive global business. Relevant education programs for students expected to be able to understand the business opportunities in entrepreneurship. The education program should be directed by a model of entrepreneurial opportunities through an integrated approach and an internship program in abroad more professional and international perspective. The internship program with overseas by working practices more effective and more facilitated with infrastructure which more adequate. By coaching and mentoring through effective and professional in the international scale indeed. Entrepreneurial education program with the apprenticeship starts from: academic learning, social learning, mental switching, cross cultural learning, and the development of the motivation for the students to have a serious intent in entrepreneurship, or graduates capable more critical thinking to face the highly prospective business opportunities in tourism this time.